Reinventing e-commerce : Amazon's bet on unmanned vehicle delivery - Walker, Russell, 1972-; Jiwani, Rafique ([London] : SAGE, 2016)
In 2013, in an interview on American television programme 60 Minutes, Amazon CEO Jeff Bezos announced that Amazon would soon change the future of online shopping by enabling customers to receive items within 30 minutes of ordering. This delivery service, Bezos said, would be powered by unmanned autonomous drones and could be offered as soon as 2015. Still, Amazon needed some answers before it could launch autonomous delivery services. This study examines Amazon's radical plans.
Originally Published in: Walker, R., & Jawani, R. (2015). Reinventing e-commerce: Amazon's bet on unmanned vehicle delivery. 5-315-501. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Amazon.com (Firm); Business logistics -- Case studies; Drone aircraft -- Case studies